Adición de fracciones (2019)
Despite the fact that fractions are related to multiple situations of everyday life, in many contexts teaching overemphasizes the processes of memorization and manipulation of algorithms (Cramer et al. 1997). In most cases, students acquire procedural knowledge to work with fractions without knowing how to explain their mathematical foundations (Freudenthal, 1983). Additionally, research has shown that students present multiple difficulties during the learning of the subject (Carpenter Coburn, Reys, & Wilson, 1976; Carpenter, Corbitt, Kepner, Lindquist, & Reys, 1980). For example, studies show that most students-aged 13 to 17 years- can add fractions with equal denominators, but only one-third of 13-year-old students can add fractions with different denominators (Behr, Lesh, Post, & Silver, 1983). Accordingly, this paper proposes a didactic unit for teaching addition of fractions. At the same time, the didactic unit promotes the learning of the topic, first, through the development of sequences of tasks that promotes the identification of concepts and procedures and the establishment of relationships between these for the use of the addition algorithm. Secondly, the didactic unit approaches the elements necessary to solve the difficulties that high school students may experience when solving situations involving the addition of fractions.--Taken from the Degree Document Format.